Depression and Executive Dysfunction in Young Adults; Implications for Therapy - B Davalos, Deana; Pantlin, Lara; Crosby, Hannah (Journal of Depression And Therapy, 2016)
The prevalence of young adults endorsing depressive symptomatology is thought to peak during late adolescence. While there has been a wealth of research assessing the relationship between decline of the prefrontal cortex and how this process impacts depression and therapy in older adults, very little is known about the relationship on the younger end of the continuum. The current study sought to explore whether there is also a significant relationship between executive functioning and depression in younger adults. In addition, different types of executive dysfunction were assessed to better understand the possible implications for therapy in younger adults with depressive symptomatology. Data from 1,730 college-aged participants were collected on measures of depression (Center for Epidemiological Studies-Depression, CES-D) and executive dysfunction (Dysexecutive Questionnaire, DEX). In addition, three factors of the DEX were assessed; Executive cognition (EC), emotional/ behavioral control (EMO), and metacognition (MC). Correlations between CES-D scores and the full DEX survey were statistically significant (R = .45, p < .001) as were correlations between CES-D scores and scores on each individual factor (p< .001). A multiple linear regression was run to demonstrate the predictive value of each individual DEX factor as a function of CES-D scores (p < .001). Results suggested that there was a clear relationship between depressive symptoms and executive dysfunction and that all factors of the DEX appeared to be affected by depressive symptoms in this population. The implications of these results for therapy, particularly the use of problem-solving therapy or complimentary executive functioning training are discussed.
Keywords: Depression; Young Adults; Dysexecutive Syndrome; Executive Functioning; College-Aged Depression; Non-Clinical Depression